2022
DOI: 10.14744/eej.2022.39200
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Final Irrigation Agitation techniques on Post-Operative Pain After Single Visit Root Canal Treatment of Symptomatic Irreversible Pulpitis (Randomized Clinical Trial)

Abstract: Objective To evaluate the degree of postoperative pain and rate of analgesic intake in patients with symptomatic irreversible pulpitis in mandibular first molar teeth at 6 h, 12 h, 24 h, 48 h, and 72 h after using different irrigation activation techniques in single-visit endodontic treatment. Methods A total of 78 patients with symptomatic irreversible pulpitis with no signs of periapical pathology were randomly divided into 3 groups according to the final irrigation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This previous study concluded that there were no statistically significant differences between the previous groups. The reason for the difference between the current study and the previous study may be due to the fact that in the current study, irrigation was activated with longer times of the three irrigants (5.25% NaOCl, 17% EDTA, and 2% CHX) that were used in the case of necrotic teeth with periapical lesions (Ali, 2022 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This previous study concluded that there were no statistically significant differences between the previous groups. The reason for the difference between the current study and the previous study may be due to the fact that in the current study, irrigation was activated with longer times of the three irrigants (5.25% NaOCl, 17% EDTA, and 2% CHX) that were used in the case of necrotic teeth with periapical lesions (Ali, 2022 ).…”
Section: Discussionmentioning
confidence: 75%
“…Some studies indicated that IAS may relieve PP in comparison with CI (Elzainy et al, 2022 ; Erkan et al, 2022 ). On the other hand, some studies did not find differences in PP levels between IAS and CI (Ali, 2022 ; Sobhy et al, 2022 ). Although CI could be a control group, the number of participants in the current study didn't help to increase the groups of the study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation